Alexithymia and autism diagnostic assessments: Evidence from twins at genetic risk of autism and adults with anorexia nervosa. (May 2020) - Hobson, Hannah; Westwood, Heather; Conway, Jane; McEwen, Fiona S.; Colvert, Emma; Catmur, Caroline; Bird, Geoffrey; Happé, Francesca
Highlights: Alexithymia has been argued to contribute to some deficits associated with autism. It is possible alexithymia affects scores on instruments such as the ADOS. This was examined in women with anorexia nervosa (AN), and adolescent twins with high autistic traits/whose twin had high autistic traits. Parent-reported alexithymia in the adolescent sample was associated with ADOS outcome, scale and item scores. In the AN sample, alexithymic women were more likely to meet diagnostic cut-off, despite few associations between scale/item scores and alexithymia. Abstract: Background: Alexithymia, a difficulty identifying and communicating one's own emotions, affects socio-emotional processes, such as emotion recognition and empathy. Co-occurring alexithymia is prevalent in Autism Spectrum Disorder (ASD) and underlies some socio-emotional difficulties usually attributed to autism. Socio-emotional abilities are examined during behavioural diagnostic assessments of autism, yet the effect of alexithymia on these assessments is not known. This study aimed to examine the associations between alexithymia and Autism Diagnostic Observation Schedule (ADOS) assessment scores. Method: Two previously collected samples of ADOS assessments were used to examine the relationship between alexithymia and ADOS scores. Participants included 96 women with anorexia, and 147 adolescents who were either high in autistic symptoms, or whose twin had high autistic symptoms. We examined 1) the impact of alexithymia on meeting the criteria for autism/ASD, 2) correlations between alexithymia and ADOS subscales, and 3) whether alexithymia predicted scores on specific ADOS items, selected a priori based on existing literature. Results: In the adolescent group, parent-reported (but not self-reported) alexithymia correlated with both ADOS sub-scales, predicted scores on ADOS items, and predicted meeting clinical cut-offs for an ASD/autism diagnosis. Few associations were observed in the anorexic sample between self-reported alexithymia and ADOS subscale and item scores, but the presence of alexithymia predicted the likelihood of meeting diagnostic criteria for autism/ASD in this sample. Conclusions: Alexithymia does show relationships with ADOS assessment scores. We discuss potential clinical and research implications, particularly in studies of autism where the ADOS is often the only diagnostic measure used.